CORRELATION OF SOCIAL EMOTIONAL LEARNING WITH THE USE OF FLIPPED CLASSROOM METHOD IN LEARNING LISTENING - Mitha Rahmawati Pellu; Nirwana. AR; Ibnu Hajar (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
The aim of this research is to find out the correlation between social emotional learning and the use of the flipped classroom method in English listening learning and to know the use of Social Emotional Learning in the application of the flipped classroom method affects English listening learning. This research used correlational research method. The subjects of this research were students of the 2021/2022 and 2022/2023 batches of the English Education study program at Iqra Buru University, totalling 35 students. The data collection technique used in this study was a questionnaire that distributed using Likert Scale. The data in this study was analysing used correlation analysis techniques in the IBM SPSS Statistic 23. Validation test has been done with the results stating that all statements in the questionnaire were valid. After calculating all valid statements, the reliability coefficient for the Social Emotional Learning questionnaire was 0,855 and the reliability coefficient for the Flipped Classroom questionnaire is 0.934. The result of this research was the significant 2-taild is 0,000 0,05 means that social emotional learning (SEL) and flipped classroom method are correlate. Besides that, the value of pearson correlation is 0,736 means that social emotional learning and flipped classroom has strong correlation and positive. The conclusion of this research is social emotional learning and the use of flipped classroom method in learning listening is correlate with strong positive correlation.